Sub-surface diagnosis for tantalite in Iseyin SW, Nigeria using magnetic survey method - Ikusika, A; Popoola, O.I (International Journal of Advanced Geosciences, 2013)
A magnetic survey was carried out at a site in Iseyin, Oyo state. The study delineates possible structures that may favour the accumulation of tantalite, a magnetic mineral. A ground based technique was employed using proton precision magnetometer G-856 AX to deduce subsurface lithology and structure that may indirectly aid the identification of mineralized rocks. A total of ten geophysical traverses were established in W-E direction in the study area. The acquired magnetic field data were corrected for drift. Qualitative and quantitative interpretations were adopted to obtain the negative peak value and the maximum positive peak value. The contour maps, image maps and the 1-grid maps present the sub-surface picture of the geological structures that are assumed to habour the metallic minerals. The study area is underlain by a rock unit of accumulated minerals. The overburden is relatively thin within the study area and the metallic minerals are in disseminated quantity and at a shallow depth.